Relative growth and sexual maturity of the spider crab Libinia spinosa Guérin, 1832 (Brachyura: Majoidea: Epialtidae), from the Southeast Brazilian coast - Santos, Mateus Pereira [UNESP]; Fransozo, Vivian; Gonçalves, Geslaine R. L. [UNESP]; Costa, Rogério Caetano da [UNESP]; Negreiros-Fransozo, Maria Lucia [UNESP] (Taylor & Francis, 2023)
We investigated the relative growth and sexual maturity (gonadal and morphometric) of Libinia spinosa. Crabs were sampled at Ubatuba from January to December 2000, using trawls. Based on allometric growth, males were grouped into juveniles (MJ), adolescents (MAd) and adults (MA) based on the relationship CPL (major cheliped propod length) vs. CW (cephalothorax width), all with positive allometric growth. For females, the relationship AW (abdomen width) vs. CW allowed segregating juveniles (FJ) from adults (FA), with positive allometric growth for FJ but isometric growth for FA. The morphometric maturity evidenced for MAd varies from 33.7 mm to 34.5 mm and for MA and FA. The size in which 50% of individuals reach the morphometric sexual maturity was L₅₀ = 50.1 mm for males and L₅₀ = 37.3 mm for females. Gonad maturity was L₅₀ = 33.7 mm for males and L₅₀ = 36.9 mm for females. Through relative growth analyses, we identified an adolescent male group (prepuberal phase). These individuals presented mature gonads, enabling them to copulate with females. These adolescent males may reproduce while avoiding competition with adult males, as it happens in other species of Majoidea that present more than two morphotypes in the population.
Keywords: Allometry; gonad development; Latitudinal variation; males morphotypes; sizeMat